Analisis Perlakuan Asap Cair Pada Serat Ampas Batang Sagu (Metroxylon Sago) terhadap Morfologi Dan Kekuatan Tarik Serat Tunggal - Mukhlis Muslimin; Bambang Tjiroso; Irwanda Yahya (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
Metroxylon sago is a palm that grows widely in tropical wetlands and has high economic and ecological value. The sago stem pulp waste contains cellulose fibers that have potential as reinforcement in composite materials. However, the hydrophilic nature and surface impurities of natural fibers limit their mechanical performance. Therefore, this study aims to analyze the effect of liquid smoke treatment on the morphology and tensile strength of single fibers from sago stem pulp. This study used an experimental method. The fibers were soaked in coconut shell liquid smoke for 1, 2, and 3 hours, followed by drying in an oven at 40°C for 30 minutes. Morphological observations were performed using a JEOL JCM 6000 Scanning Electron Microscope, and single fiber tensile tests were conducted according to ASTM D3379-02 standard. The results were compared with untreated fibers as control. The results showed that liquid smoke treatment altered the fiber morphology in all treatment variations. The most optimal surface morphology was obtained at 1 hour of treatment, characterized by a cleaner and rougher surface due to the removal of hemicellulose and impurities. In terms of mechanical properties, liquid smoke treatment increased the tensile strength of single fibers. The highest tensile strength was achieved at 1 hour of treatment with a value of 49.232 MPa, while the lowest was at 2 hours of treatment with 16.694 MPa. Prolonged soaking beyond 1 hour caused fiber degradation and a decrease in tensile strength. It can be concluded that 1 hour of liquid smoke treatment is the optimum duration to improve the morphology and tensile strength of single sago stem pulp fibers. This treatment can be used as an environmentally friendly alternative to enhance the quality of natural fibers for composite reinforcement applications.